Optimization of Supercritical Extraction Conditions of Senna Alata and Evaluation of Biological Activity - Subuki, Istikamah; Nabilah Abdul Malek, Aiman; Husni Saidin, Saidatul; Md. Pisar, Mazura (International Journal of Engineering and Technology, 2018)
Supercritical fluid extraction (SFE) offer faster extraction process, decreased solvent usage and more selectivity on desired compounds. In this present study, the influence of pressure (100, 200 and 300 bar) and temperature (40, 50 and 60ËšC) on the Senna alata crude yield were investigated with fixed supercritical carbon dioxide (SC-CO2) at the flow rate of 35 g/min. The parameters were optimised and modelled using response surface methodology (RSM) and central composite design (CCD). The analysis of variance (ANOVA) experimental design consists of 13 experimental runs with 5 replicates at the central points. Well-fitting quadratic model were successfully established for crude extract through backward elimination. The optimum crude extract yield pointed out by RSM was at the pressure of 300 bar and temperature 40ËšC respectively. Extraction yields based on SC-CO2 varied in the range of 0.28 to 3.62%. The highest hyaluronidase inhibition activity and total flavonoids content obtained by S.alata crude extracts were 41.19% and 52.53% w/w, respectively. SC-CO2 proves to have great potential for extraction of yield, hyaluronidase inhibition activity and total flavonoids content for S.alata.Â Â